FAKTOR-FAKTOR PENYEBAB KETIMPANGAN PENDAPATAN DI KABUPATEN WAJO - Misbahuddin Misbahuddin (AkMen JURNAL ILMIAH, 2017)
The purpose of this study to determine the factors - factors that cause inequality in the district Wajo South Sulawesi province, which so far has always been a measure of success of economic development measured by the rate of economic growth of a region. Methods using survey method with a sample size of 300 people by the criteria of the lowlands, coastal sea. Coastal lakes and urban areas. The analytical method used is the Gini index ratio with the standard of the World bank by category according to criteria Gini ratio imbalance. Data collection method used is survey conducted on four groups of regions (City, Plains / Peranian, Coastal and Coastal lake) by using the technique of cluster sampling and then split three income brackets (Poor, Medium, Dan Rich), with the technique proportionate stratified random sampling. Results research the Gini index calculation sub-districts in urban areas Tempe shows inequality value of 0.67, or it can be said that there is high inequality (G1> 0.5) The calculations show that the sub-district agricultural area Maniangpajo, with income from rice farming to the level high inequality but still below inequality in urban areas, it is visible from a Gini index of 0,61.Indeks gini coastal area lakes Tanasitolo subdistrict of 0.67 indicates that this wiliyah have a society with high income inequality, while coastal areas are represented by the District have the ball gini index of 0.61 which indicates that this wlayah have income groups with high inequality.